The impact of management compliance attention and board faultlines strength on ESG performance: Evidence from Chinese listed companies - Yong Jiang; Fei Han (PLoS ONE, 2025)
Against the backdrop of global sustainable development goals and the rapid evolution of ESG practices in China, this study empirically examines how management compliance attention and board faultlines strength affect ESG performance using data from Chinese A-share listed companies spanning 2010–2022. Using textual analysis of annual reports to measure compliance attention, we employ OLS (Ordinary Least Squares) regression, moderation, and mediation analyses. The findings reveal three key results: (1) Management compliance attention is positively associated with ESG performance (β = 0.041, p < 0.01); (2) Board faultlines strength significantly amplifies this positive impact (β = 0.114, p < 0.01); (3) Organizational resilience partially mediates the relationship between management compliance attention and ESG performance, as confirmed by a Sobel test (z = 3.089, p = 0.002). Heterogeneity analysis shows that state-owned enterprises exhibit more pronounced compliance-driven ESG improvements, whereas private firms rely on board diversity to enhance such effects. This study contributes to the literature by integrating institutional theory, cognitive theory, upper echelons theory, and dynamic capabilities theory, demonstrating that management compliance attention boosts ESG performance through organizational resilience, with board faultlines acting as a critical moderator. Practical implications include recommendations for firms to strengthen compliance cultures, foster diverse boards, and build organizational resilience, while policymakers should enhance compliance frameworks and ESG disclosure standards to promote sustainable corporate practices.